Judicial Dispute Resolution in Canada: Towards Accessible Dispute Resolution - Zariski, Archie (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
This article argues that access to judges is an essential element of access to justice. Traditional civil litigation procedure aimed at preparation for trial that is complex, time-consuming and costly obstructs such access, especially for litigants without lawyers. To remedy this, the author proposes a summary judicial dispute resolution procedure comprising two stages: early judicial intervention followed by judicial dispute resolution that is determinative if necessary. At both points litigants would be given the opportunity to settle their dispute consensually, thus combining principles of self-determination with final disposition according to law. The proposal draws on and extends contemporary innovations in Canadian courts concerning summary proceedings and binding judicial dispute resolution. The new procedure should improve access to judges and thus access to justice.